Conclusion Empirical Equations of Asymmetry Parameter for Magic Nuclei in N for()α,n Reaction of Incident Neutron Energy (14.5 MeV) - Al-Attabi, Hadi (Iraqi Journal of Science, 2024)
In this study, the magic nuclei is divided into two groups, one of them is light group and the other is middle group, it was calculated shell corrections for all nuclei, and also it was concluded the relationship between cross sections for nuclear reactions ()α,n and the mass number (A) for all nuclei to incident neutrons (14.5 MeV). We found empirical equations to asymmetry parameter (N-Z)/A as function of mass number and for that two groups: for A=38 to A=40 light nuclei.()0534.10263.0+−=−AAZN for A=50 to A=89 middle nuclei. ()408.00151.00001.02−+=−AAAZN for A=90 to A=144 middle nuclei. ()0711.10221